2015
DOI: 10.1007/s11655-015-2181-7
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antifungal activity of some traditional Persian medicinal plants on pathogenic fungi

Abstract: If the antifungal activity of P. olivieri is confirmed by in vivo studies and if the responsible compound (s) is isolated and identified, it could be a good remedy for mycotic infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…Numerous studies have considered the antimicrobial screening of traditional plant extracts. The studies of medicinal plants from diverse topographical areas include: Armenia [65], Iran [66], Mexico [67], Saudi Arabia [68], Libya [26], Ethiopia [64], India [63], Poland [69], Cameroon [70], Nigeria [71], and other Middle Eastern countries [72]. Based on the available information, the traditional plant extracts showed antimicrobial activity against a huge number of pathogenic bacteria, fungi, viruses, algae, protozoan, and Trypanosoma [26,63,64,66].…”
Section: Phytocomponent Fractions and Antimicrobial Methodsmentioning
confidence: 99%
“…Numerous studies have considered the antimicrobial screening of traditional plant extracts. The studies of medicinal plants from diverse topographical areas include: Armenia [65], Iran [66], Mexico [67], Saudi Arabia [68], Libya [26], Ethiopia [64], India [63], Poland [69], Cameroon [70], Nigeria [71], and other Middle Eastern countries [72]. Based on the available information, the traditional plant extracts showed antimicrobial activity against a huge number of pathogenic bacteria, fungi, viruses, algae, protozoan, and Trypanosoma [26,63,64,66].…”
Section: Phytocomponent Fractions and Antimicrobial Methodsmentioning
confidence: 99%
“…It is noticed that M. oleifera oil gave the most significant inhibitory effect against all tested Candida isolates as MIC of M. oleifera oil was 1%. According to Asgarpanah et al (2017), who found that M. oleifera oil gave high antimicrobial activity. Similarly, Siddhuraju & Becker (2003) showed that M. oleifera seed oil was very effective for infectious diseases, inflammation treatment and antimicrobial activities.…”
Section: Antifungal Activity Of M Oleifera Seed Extracts and Oilmentioning
confidence: 99%
“…The use of dwarf elder has been recommended as an anti-fungal remedy against mycotic skin infections [119] and as a painkiller to treat a variety of bone and joint pathologies [120]. In addition, the aqueous extract of castor bean leaves has been mentioned to alleviate the pain induced by chronic knee osteoarthritis [118].…”
Section: Unani Medicinementioning
confidence: 99%